The fundamental theorem of algebra for polyanalytic polynomial - Balk, M. (Lithuanian Mathematical Journal, 1968)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: М. Б. Балк. Основная теорема алгебры для полианалитических полиномов M. Balkas. Pagrindinė algebros teorema polianalizinių polinomų atveju